Short communication. Telluric pathogens isolated from blighted pepper (Capsicum annuum L.) plants in northwestern Spain - Andres Ares, J.L.=700 1 Rivera Martinez, A.; Pomar Barbeito, F.; Fernandez Paz, J.
(Es, En)
ilus., 29 ref.
Keywords: CAPSICUM ANNUUM; FUSARIUM SOLANI; ORGANISMOS PATOGENOS; MARCHITEZ; PHYTOPHTHORA NICOTIANAE; PODREDUMBRE DEL CUELLO DE LA RAIZ; ESPAÑA